Hypolipidemic and Hypoglycaemic Effect of Wholemeal Bread with Amaranth (Amaranthus dubius Mart. ex Thell.) on Sprague Dawley Rats - Adriana Beatriz Sánchez-Urdaneta; Keyla Carolina Montero-Quintero; Pedro González-Redondo; Edgar Molina; Belkys Bracho-Bravo; Rafael Moreno-Rojas (Foods, 2020)
The effect of consuming breads made with wheat flour and Amaranth (Amaranthus dubius Mart. ex Thell.) wholemeal flour on Sprague Dawley rats with hyperlipidaemia and hyperglycaemia induced through feeding was studied. Four diets were provided: control (CD: Ratarina®), commercial bread (CBD), bread with 100 g·kg−1 (ABD10) and 200 g·kg−1 (ABD20) amaranth flour. Zoometric and blood chemistry parameters were measured before and after consuming the diets. A completely random factorial design of 2 × 4 × 2 was used. The factors were blood lipids and glucose level (normal, N and elevated, E), diet (CD, CBD, ABD10 and ABD20) and sex (female, F and male, M). The rats consuming ABD10 and ABD20 diets presented the lowest glucose values, although with no differences (p > 0.05) between the groups of elevated blood lipids and glucose rats (E). Triglyceride concentrations decreased in ABD10 and ABD20 treatments in comparison with CD, elevated blood lipids and glucose (E) rats, while ABD10 rats showed lower total cholesterol level than normal (N) rats. The high-density lipoprotein cholesterol values increased in the ABD10 and ABD20 groups (p < 0.05), while it did lower for very low-density lipoprotein cholesterol and cardiac risk index (p < 0.05). In ABD10 and ABD20 treatments, the abdominal circumference decreased in both sexes (p < 0.05) between weeks 23 and 31. In conclusion, consumption of bread with amaranth improved lipid profiles of rats and could help to prevent metabolic and cardiovascular diseases.